Determination of the inductance of imploding wire array Z-pinches using measurements of load voltage - Burdiak,GC; Lebedev,SV; Hall,GN; Harvey-Thompson,AJ; Suzuki,Vidal F; Swadling,GF; Khoory,E; Pickworth,L; Bland,SN; de,Grouchy P; Skidmore,J (Physics of Plasmas, 2013)
The inductance of imploding cylindrical wire array z-pinches has been determined frommeasurements of load voltage and current. A thorough analysis method is presented that explainshow the load voltage of interest is found from raw signals obtained using a resistive voltagedivider. This method is applied to voltage data obtained during z-pinch experiments carried out onthe MAGPIE facility (1.4 MA, 240 ns rise-time) in order to calculate the load inductance andthereafter the radial trajectory of the effective current sheath during the snowplough implosion.Voltage and current are monitored very close to the load, allowing these calculations to be carriedout without the need for circuit modelling. Measurements give a convergence ratio for the currentof between 3.1 and 5.7 at stagnation of the pinch.